Hermeneutics of Reception by Hans Robert Jauss: An Alternative Approach Toward Quranic Studies - Lathifatul Asna; Nasihun Amin (International Journal Ihya' 'Ulum al-Din, 2022)
This research attempts to offer hermeneutics of reception by Hans Robert Jauss as an alternative to understanding the Quran. Starting from the concern of some contemporary Islamic thinkers about the limitations of the classical Quran in overcoming human problems that are always dynamic, hermeneutics has become a much-demanded approach. In addition, the methodological principle of classical interpretation tends to forget the role of human participation in interpreting the Quran. Nevertheless, the practice of the reception approach has stagnated in the study of the living Quran, which only performs a simple analysis of a tradition into three reception typologies: exegesis, functional, and aesthetic, without any more profound critique. This article aims to describe Hans Robert Jauss’ hermeneutics of reception as a relevant offer to fill the void of Quranic studies from the reader's perspective. For this reason, this article is compiled using qualitative methods based on literature studies so that essential aspects that need to be considered as material for hermeneutics of reception analysis can be well elaborated. There are three crucial aspects to the hermeneutics of reception; the Horizon of expectations, the three levels of reading, and the validity of the aesthetic experience.